The Influence of the Problem Based Learning Model Assisted by PhET Simulation on Students' Learning Outcomes in Parabolic Motion Material - Dian Molamahu; Trisnawaty Junus Buhungo; Citron S. Payu (Physics Education Research Journal, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model assisted by PhET Simulation on students' learning outcomes in parabolic motion material in Grade XI-Physics at SMA Negeri 1 Suwawa. This research is experimental with a One Group Pretest-Posttest Design. The sampling technique used in this study is total sampling. The population includes all Grade XI students majoring in Physics at SMA Negeri 1 Suwawa for the 2024/2025 academic year, consisting of three classes. The sample includes the entire population: Class XI A as the experimental class, Class XI C as the first replication class, and Class XI B as the second replication class, determined randomly through a lottery method. The data collection technique was conducted using a test in the form of 10 essay questions that had been validated by expert lecturers. The data obtained from the tests were analyzed using statistical tests, including the Liliefors normality test, hypothesis testing, and N-gain analysis. Based on the research results, the average posttest scores were 84.3 for the experimental class, 79.7 for the first replication class, and 82.8 for the second replication class. The hypothesis test results showed that the average scores of all sample classes were higher than the minimum passing score (KKM), which is 70. Based on the analysis of the course average normalized gain, the experimental class achieved 0.78, the first replication class 0.72, and the second replication class 0.75, indicating a high category for all sample classes. Thus, the use of the PBL model assisted by PhET Simulation significantly affects high school students' learning outcomes in parabolic motion material.